1975
DOI: 10.1159/000180516
|View full text |Cite
|
Sign up to set email alerts
|

Kidney and Adrenocortical Hormones

Abstract: We have presented a review of the interrelationship between the kidney and the adrenocortical steroids, aldosterone and cortisol, primarily in the regulation of water and electrolyte metabolism. The presentation is divided into three parts: (1) the influence of cortisol and aldosterone on renal structure and function; (2) the effect of kidney disease on secretion and metabolism of these steroids, and (3) the role of the kidneys in the plasma clearance of these steroids and their metabolites. There is no eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 64 publications
(148 reference statements)
2
15
0
Order By: Relevance
“…Moreover, these rats had significantly decreased urinary output during the entire experimental period (Fig. 1A), consistent with previous observations of impaired water excretion in response to glucocorticoid deficiency (23,24,29,41). In contrast, rats with aldosterone deficiency had significantly increased urinary output at the early stage after ADX (days 1-4, Fig.…”
Section: Glucocorticoid Deficiency and Mineralocorticoid Deficiency Isupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, these rats had significantly decreased urinary output during the entire experimental period (Fig. 1A), consistent with previous observations of impaired water excretion in response to glucocorticoid deficiency (23,24,29,41). In contrast, rats with aldosterone deficiency had significantly increased urinary output at the early stage after ADX (days 1-4, Fig.…”
Section: Glucocorticoid Deficiency and Mineralocorticoid Deficiency Isupporting
confidence: 91%
“…The observed decrease in urinary output is consistent with previous studies demonstrating that glucocorticoid deficiency is associated with an impaired water diuresis (19,23,29,41) and glucocorticoid treatment has been shown to restore this defect (29), partly by augmenting atrial natriuretic peptide (ANP) action (18). The impaired excretion of water by the kidney in glucocorticoid deficiency has been extensively investigated (1,16,19,24,29,41).…”
Section: Changes In Water Metabolism In Response To Glucocorticoid Desupporting
confidence: 88%
See 1 more Smart Citation
“…However, as the decline in blood pressure and glomerular filtration was not apparent in animals in which only the posterior lobe ofthe pituitary had been removed (Balment, Brimble, Forsling, Kelly & Musabayane, 1986), it would appear to result from the loss of one or more of the anterior pituitary factors, or of the hormones whose secretion they regulate. There is indeed evidence that glomerular filtration is impaired if glucocorticoid secretion is reduced to low levels as a result of loss of pituitary corticotrophin (Cutler, Kleeman, Koplowitz, Maxwell & Dowling, 1962;Kleeman, Levi & Better, 1975), and it has been shown that administration of exogenous corticotrophin can partially restore arterial blood pressure and glomerular filtration in chronically hypophysectomized rats (Bauman, 1967;Bauman & Phillips, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…As the kidney matures it becomes capable of increasing distal tubular sodium reabsorption to compensate for any increased distal tubular fluid delivery. (Pediatr Res 26: [6][7][8][9][10]1989) Abbreviations FRN,, fractional reabsorption of sodium FR,,i, fractional reabsorption of lithium uN,,v, uKV, UclV, Uc.V, renal excretion rate of sodium/ potassium/chloride/calcium may be responsible for neonatal hyponatremia. However, subsequent investigations have shown that a characteristic of this defect is decreased proximal tubule reabsorption of sodium (2) implying that renal insensitivity to aldosterone may be only partially responsible.…”
mentioning
confidence: 99%